PENGUATAN HAK-HAK MASYARAKAT HUKUM ADAT AMMATOA KAJANG SEBAGAI WUJUD REALISASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 35/PUU-X/2012 - Imran K; Aswan sidrap; Wardiman Anugrah Pratama (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2020)
AbstractTo find out the strengthening of the customary rights of ammatoa kajang through the protection of the existence of customary forests in national regulations and legislation and to find out the legal consequences of the decision Mahkamah Konstitusi Number 35/PUU-X/2012 on the existence of customary forests. Protection of customary forests in legislation cannot be separated from the recognition of the customary law community first. In the legislation has become a challenge for the existence of indigenous peoples, Pasal 18B Ayat 2 UUD 1945 became the basis for the protection of the community the customary law stipulated in the Regional Regulations recognizing customary law communities, Pasal 67 Ayat 2 UU No. 41 About Forestry. With public awareness of the functions of forests, the Ammatoa customary law community will always maintain the forest sustainability. If not, they themselves will feel the consequences. There will be drought and crop failure, and will not be able to carry out other activities which are always explained by them